"And she does it all in heels": mothers in contemporary Israeli TV commercials. Issue 2 (4th March 2017) - Barak-Brandes, Sigal
Abstract: Although numerous studies have examined the image of women in advertising, the current study is exceptional in looking at the representations of motherhood and mothering practices in contemporary Israeli TV commercials, in an attempt to shed light on the ideological messages they reflect and promote. Sixty-four TV commercials were analyzed using critical discourse analysis. In many ads the mother is depicted as aesthetically pleasing and shapely. This inclusion of the beauty myth in all its cruel demands into the can-do mother myth, could lead Israeli women to a sense of failure as they compare themselves to the glamorous image in the ads and invariably fall short. The hetero-couple-headed nuclear family shown in many ads seems to be a conservative manifestation of the assumption that the "good mother" exists only in the framework of the normative family unit. It seems that in the context of the advertising genre, these are products that lie at the heart of family and couple relationships, and that it is therefore possible to speak of the commodification of the family. The study also found progressive images of the clever, resourceful mother alongside the pathetic, ridiculed one—a new kind of a "bad mother."